Information and communication technology development in Malaysia: influence of competency of leaders, location, infrastructures and quality of services on telecentre success in rural communities of Malaysia - Bashir, Muhammad Sani; Abu Samah, Bahaman; Emby, Zahid; Badsar, Muhammad; Mohamed Shaffril, Hayrol Azril; Aliyu, Abdulra’uf (American-Eurasian Network for Scientific Information, 2011)
In recent years, Local information and communication centers popularly referred to as telecentres have been emerging all over in developing countries, with the objective of bridging digital divide and bringing the benefit of information and communication technology (ICT) to the rural poor. However, there is no clear understanding about factors influencing their success. The study examines the influence of competency of leaders, location, infrastructure and quality of services on telecentre success in rural communities of Malaysia. The study employed quantitative research methodology, utilizing self administered questionnaire. Stratified random sampling was used in selecting the respondents. A total of 138 respondents from 11 community telecentre called Pusat Internet Desa (PIDs) in four states in Peninsular Malaysia were involved in this study. Data collected were analyzed using SPSS, employing descriptive statistics, Pearson correlation and step wise multiple regression analyses. The results of the Pearson correlation analyses revealed that there were significant positive relationships between competency of leaders, location, infrastructures, quality of services and telecentre success.Based on the finding of step wise multiple regression, competency of leaders and Infrastructures contribute significantly toward telecentre success. Base on the findings it can be concluded that competency of leader, location, infrastructures and quality of services have significant influence on telecentre success. Also base on the findings of the regression analysis it can be concluded that competency of leaders and infrastructures are important factors that are significantly contributing towards telecentre success.